LEACHING AND CARRYOVER FOR SAFRINHA CORN OF THE HERBICIDES IMAZAPYR + IMAZAPIC IN SOIL UNDER DIFFERENT WATER CONDITIONS - Souza, Amanda dos Santos (2020)
Soil moisture can alter the transport and permanence of pre-emergent herbicides. The objective of this work was to evaluate the influence of water availability in the soil on the leaching of a commercial mixture of the herbicides imazapyr + imazapic, as well as the carryover effect of this herbicide in corn planted in succession to soybean. The experiment was carried out in leaching columns in a randomized block design with 4 replications. A 3x3x2 factorial scheme was used, with factor A being the irrigation (130%, 100% and 70% of field capacity (CC)), factor B the doses of the commercial mixture of the herbicides imazapyr + imazapic (0.00+ 0.00; 52.5 + 17.5 and 105 + 35 g ha-1) and factor C at soil depth (0-0.3 m and 0.3-0.6 m). Soybean sowing was performed at the top of the columns and immediately after herbicide mixture was applied. After 120 days the columns were opened, generating two sections, where corn (Zea mays) and the other watermelon (Citrullus lanatus) were sown as a bioindicator of herbicide residue. The fluorescence parameters of chlorophyll a at 15 and 30 days after germination (DAG) and shoot dry matter accumulation at 30 DAG were evaluated. There was greater retention of the herbicide imazapyr + imazapic at a depth of 0-0.3m at 70% CC condition and leaching at a depth of 0.3-0.6m at 130% CC condition, with a reduction in the mass accumulation of watermelon plants. The herbicide has a carryover potential for corn cultivation in soils maintained at 70% CC.